Strategic location behaviour: Temporal and spatial proximity in situation of agglomeration effects - Thierry Mayer; Jean-Louis Mucchielli (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
We address the question of competition within the location choices of firms. In a framework of agglomeration effects, both spatial and temporal dimensions of the firms' decisions are studied. We show that the competition consequences of preemptive move and optimal time of entry can interfere with the geographical decisions. Our results contrast with those of agglomeration economics models which generally provide extreme results of mono-location. The Stackelberg equilibria described here tend to demonstrate that the relation between competition strength and spatial differentiation remains pertinent in a context of agglomeration economies.
Keywords: F21; 330; location theory; agglomeration effects; strategic investment; Auslandsinvestition; Standorttheorie; Agglomerationseffekt; Duopol; Wettbewerb; Theorie